FAO fisheries synopsis; Vol.18; No.125 - Jorge Nielsen...[et al.] (FAO, 1999)
This book cobers all 93 genera currently recognized in the order Ophidiformes (pearfishes, cusk-eels, brotulas and allies). It includes a glossary of technical terms, general remarks on the order, identification keys from the suborder to the species level, detailed genera accounts, and a table in illustrated accounts.